Effects of Sc and Be Microalloying Elements on Mechanical Properties of Al-Zn-Mg-Cu (Al7xxx) Alloy - Sung-Jae Won; Hyeongsub So; Jung-Woo Han; Soong Ju Oh; Leeseung Kang; Kyou-Hyun Kim (Metals, 2023)
We demonstrate via comprehensive microstructural investigation the effects of Sc and Be microalloying on the mechanical properties of Al-Zn-Mg-Cu-based alloys, where Sc microalloying enhances the tensile properties of an Al-9.0Zn-3.0Mg-3.0Cu alloy from 645 MPa (εf = ~6%) to 672 MPa (εf = ~8%). In contrast, simultaneous microalloying with Sc and Be reduces the mechanical strength of a synthesized Al alloy to 654 MPa (εf = ~8%). Comprehensive microstructural investigation revealed that Sc microalloying leads to Al grain refinement, the formation of hardening (MgZn2, Al3M) phases, and an increase in the solid solution of Al. Additional Be microalloying also enhances the formation of MgZn2 phase, while Al3M (M: Zr, Sc) type phases are restrained from forming in Al grains. Furthermore, solid solution in Al grains is reduced by the trace addition of Be microalloying, resulting in an increase in large intermetallic compounds at Al grain boundaries.